Striking a Balance in Communicating Pharmacogenetic Test Results: Promoting Comprehension and Minimizing Adverse Psychological and Behavioral Response - Haga, Susanne B. (2014)
OBJECTIVE: Pharmacogenetic (PGx) testing can provide information about a patient’s likelihood to respond to a medication or experience an adverse event, and be used to inform medication selection and/or dosing. Promoting patient comprehension of PGx test results will be important to improving engagement and understanding of treatment decisions METHODS: The discussion in this paper is based on our experiences and the literature on communication of genetic test results for disease risk and broad risk communication strategies. RESULTS: Clinical laboratory reports often describe PGx test results using standard terminology such as ‘poor metabolizer’ or ‘ultra-rapid metabolizer.’ While this type of terminology may promote patient recall with its simple, yet descriptive nature, it may be difficult for some patients to comprehend and/or cause adverse psychological or behavioral responses. CONCLUSION: The language used to communicate results and their significance to patients will be important to consider in order to minimize confusion and potential psychological consequences such as increased anxiety that can adversely impact medication-taking behaviors. PRACTICE IMPLICATIONS: Due to patients’ unfamiliarity with PGx testing and the potential for confusion, adverse psychological effects, and decreased medication adherence, health providers need to be cognizant of the language used in discussing PGx test results with patients.